STRATEGI PENGUATAN KEMAMPUAN BACA-TULIS DAN HITUNG PADA ANAK-ANAK DENGAN PENINGKATAN GRAFIS MELALUI KARTU FLASH DI SLB X KUDUS - Fatmawati, Nurul Fidya; Rohmah, Sinvi Faido; Ruby, Arcivid Chorynia (Yayasan Amanah Nur Aman, 2025)
This study aims to determine how the use of flashcard media can help improve basic literacy and numeracy skills in mildly mentally retarded students at SLB X Kudus. Mentally retarded students generally have difficulty in understanding letters and numbers due to cognitive limitations, memory, and concentration, so they need a concrete and enjoyable learning approach. This study uses a qualitative approach with a case study method on one student in class VIII-C1 with the initials DK. Data were collected through observation, interviews, and documentation during eight learning meetings. The results showed that before the use of flashcards, DK was not yet able to recognize vowels, distinguish consonants, mention numbers 1–10, and match numbers with the number of objects. After the flashcards were consistently applied, DK showed an increase in learning interest, focus, and the ability to recognize and mention letters and numbers in a guided manner. The discussion confirms that flashcard media which is visual, interesting, and interactive is suitable for the learning style of mentally retarded children who find it easier to understand concrete information. In conclusion, flashcards have proven effective in supporting the development of basic literacy and numeracy in mildly mentally retarded students, and can be a relevant visual learning strategy in the context of inclusive education.